2020
DOI: 10.7250/csimq.2020-22.04
|View full text |Cite
|
Sign up to set email alerts
|

Usability as Speculum Mundi: A Core Concept in Socio-technical Systems Development

Abstract: Usability covers the breadth and depth of the rich interaction of users and technology in the socio-technical context. Though the concept of usability is well established, the integration of usability thinking in system development is challenging, partly due to the difficulty in understanding the importance of usability and justifying the costs incurred by usability work. This article aims to bring forth three fundamental attributes of usability that originate in classical architecture design, namely, utilitas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Such a standardized definition can enable goals and measurements to be unified in the domain of service experience but is missing in the context of WFH. Some researchers (Bentley et al, 2016;Rajanen & Rajanen, 2020) have suggested that people's experience of complex sociotechnical systems is usually determined by a subjective reaction to objective aspects and constraints. Therefore, it seems plausible that the interplay between a subjective reaction and objective aspects is a determinant in the quality experienced by people in WFH modalities.…”
Section: Experience Of Working From Home Remotelymentioning
confidence: 99%
“…Such a standardized definition can enable goals and measurements to be unified in the domain of service experience but is missing in the context of WFH. Some researchers (Bentley et al, 2016;Rajanen & Rajanen, 2020) have suggested that people's experience of complex sociotechnical systems is usually determined by a subjective reaction to objective aspects and constraints. Therefore, it seems plausible that the interplay between a subjective reaction and objective aspects is a determinant in the quality experienced by people in WFH modalities.…”
Section: Experience Of Working From Home Remotelymentioning
confidence: 99%
“…However, traditional HCI that involves users in system design can offer a limited viewpoint for the broad and global transformations that occur in society. Contemporary technology and information systems not only influence end users but also have holistic effects on society at large (Rajanen & Rajanen, 2019).…”
Section: A Broad Interpretation Of Hci In a Sharing Societymentioning
confidence: 99%
“…Researchers have begun to refine key UX and usability concepts to fit the information technology in the age of collaboration and sharing (Abhari, Davidson, & Xiao, 2019). Usability represents a core concept in socio-technical system development because it impacts how users and society perceive and experience technology-driven transformations, and it acts as a mirror of the world or speculum mundi (Rajanen & Rajanen, 2019). This special issue contributes to the emerging body of knowledge on HCI in a sharing society.…”
Section: Hci In a Sharing Societymentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptually, and from a theoretical perspective, usability concerns the rich interaction of users and technology in a socio-technical context [ 13 ]. Usability may even be viewed as part of the higher-level concept of interaction experience, together with user experience (including aesthetics, trust, value, affect) and accessibility [ 14 ].…”
Section: Introductionmentioning
confidence: 99%